Effects of Insulin-Like Growth Factor-I on the Expression of Atrogin-1/MAFbx in Chick Myotube Cultures - Kazuki Nakashima; Aiko Ishida; Saki Shimamoto; Daichi Ijiri; Akira Ohtsuka (The Journal of Poultry Science, 2017)
The expression of atrogin-1/MAFbx, a muscle-specific E3 ubiquitin ligase, is increased in catabolic conditions that result in muscle atrophy. The expression of atrogin-1/MAFbx mRNA is also decreased by the insulin-like growth factor-I (IGF-I) in mammalian skeletal muscle cell cultures. This study investigated the effect of IGF-I on the expression of atrogin-1/MAFbx in chicken skeletal muscle cell cultures. Chick myotubes were incubated with IGF-I for 1, 6, or 24 h. Protein content was increased by IGF-I (100 ng/ml) and incubated for 24 h in chick myotubes. The expression of atrogin-1/MAFbx mRNA decreased in the presence of IGF-I (1, 10, and 100 ng/ml) for 6 h in chick myotubes. The expression of the m-calpain large subunit and cathepsin B mRNA was not decreased by IGF-I. Phosphorylation of Akt and FOXO1 increased in the presence of IGF-I (100 ng/ml) for 1 h in chick myotubes. These results indicate that IGF-I suppresses atrogin-1/MAFbx mRNA expression by phosphorylation of Akt and FOXO1, resulting in an increase in muscle growth in chick myotube cultures.